2019
DOI: 10.1108/ijcma-12-2018-0142
|View full text |Cite
|
Sign up to set email alerts
|

Process conflict and employee well-being

Abstract: Purpose The primary objective of this paper is to extend the Activity Reduces Conflict Associated Strain (ARCAS) model. To test the ARCAS model, the study aims to examine the effect of process conflict on employee well-being and the role of negative affect as an intrapersonal mechanism linking process conflict and employee well-being. Further, to extend the emerging ARCAS model, the study examines whether the assumed indirect effect of process conflict on employee well-being through negative affect is conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 114 publications
3
19
0
Order By: Relevance
“…For example, Danielsson et al (2015) reported that among thousands of participants in their studies over the past two years, 84% had reported being in some type of conflict situation with their coworkers, and about 50% had experienced it on a weekly basis. In addition to its high prevalence, interpersonal conflict has been found to have detrimental effects on employee job attitudes, health and well‐being, nonwork life and performance (for reviews, see Bonaccio et al , 2019; Kuriakose et al , 2019; Notelaers et al , 2018; Ye et al , 2019). In addition to the negative effects of interpersonal conflict on individuals’ work and health‐related outcomes, Zhou et al (2019) suggest that effects of interpersonal conflict at work can spill over to employees’ negative work behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Danielsson et al (2015) reported that among thousands of participants in their studies over the past two years, 84% had reported being in some type of conflict situation with their coworkers, and about 50% had experienced it on a weekly basis. In addition to its high prevalence, interpersonal conflict has been found to have detrimental effects on employee job attitudes, health and well‐being, nonwork life and performance (for reviews, see Bonaccio et al , 2019; Kuriakose et al , 2019; Notelaers et al , 2018; Ye et al , 2019). In addition to the negative effects of interpersonal conflict on individuals’ work and health‐related outcomes, Zhou et al (2019) suggest that effects of interpersonal conflict at work can spill over to employees’ negative work behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the current study aims to extend the previous research on negative outcomes of interpersonal conflict by examining the relationship between interpersonal conflict and CWB. Moreover, prior research shows that the effect of interpersonal conflict varies across individuals indicating the presence of moderators regulating the relationship between interpersonal conflict and its outcomes (Kuriakose et al , 2019). Therefore, in addition, we investigate a moderated-moderation analysis, considering two conditional effects – employees’ emotional intelligence (high vs. low) and gender (men vs. women) – as potential moderators.…”
Section: Introductionmentioning
confidence: 99%
“…had reported being in some type of conflict situation with their coworkers, and about 50% had experienced it on a weekly basis. In addition to its high prevalence, interpersonal conflict has been found to have detrimental effects on employee job attitudes, health and well-being, nonwork life and performance (for reviews, see Bonaccio et al, 2019;Kuriakose et al, 2019;Notelaers et al, 2018;Ye et al, 2019). In addition to the negative effects of interpersonal conflict on individuals' work and health-related outcomes, Zhou et al (2019) suggest that effects of interpersonal conflict at work can spill over to employees' negative work behaviors.…”
Section: Emotional Intelligence and Gendermentioning
confidence: 99%
“…Accordingly, the current study aims to extend the previous research on negative outcomes of interpersonal conflict by examining the relationship between interpersonal conflict and CWB. Moreover, prior research shows that the effect of interpersonal conflict varies across individuals indicating the presence of moderators regulating the relationship between interpersonal conflict and its outcomes (Kuriakose et al, 2019). Therefore, in addition, we investigate a moderated-moderation analysis, considering two conditional effectsemployees' emotional intelligence (high vs. low) and gender (men vs. women)as potential moderators.…”
Section: Emotional Intelligence and Gendermentioning
confidence: 99%
“…Dealing effectively with conflicts in the workplace is a necessary skill for success (Ayub et al, 2017). The way employees and managers deal with conflicts influences their opinions, emotions and behaviors toward their conflict partner and toward their workplace (Kuriakose et al, 2019). Research has found that conflict management styles influence organizational outcomes such as performance, organizational commitment, job satisfaction and the efficacy of influence tactics in obtaining compliance (Mossholder et al, 1998;Pierro et al, 2012;Schwarzwald et al, 2004).…”
Section: Introductionmentioning
confidence: 99%